Socioeconomic Development Strategy for Remote Pulau Maringkik Village, East Lombok Regency: A SWOT Analysis - Tati Atmayanti; Muhammad Malthuf; Hasbulloh Nadaraning; Baiq Dewi Lita Andiana (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2026)
This study aims to examine financial distress studies based on Scopus and SINTA databases. Based on the PRISMA method, 87 articles were determined. Trends in studies increased every period, except in 2018. A total of 20 financial variables and 22 non-financial variables were identified. The non-financial sector was the most sampled in the studies. The Z-Score model is the best model for predicting financial distress while the most popular theory is agency theory. The most-cited articles entitled The Effects of Ownership Structure on Likelihood of Financial Distress: An Empirical Evidence and The Effect of Leverage, Sales Growth, Cash Flow on Financial Distress with Corporate Governance as a Moderating Variable. Global studies are dominated by non-financial variables with nine author clusters, whereas Indonesian studies are dominated by financial variables with six author clusters. This study identifies research gaps in financial distress literature and informs early warning systems for stakeholders.